An evaluation of HIV/AIDS management training conducted to school management teams in the Free State Department of Education - Lejweleputswa district - Stephen, Kgotso Eric (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.